2009
DOI: 10.1029/2008jb006280
|View full text |Cite
|
Sign up to set email alerts
|

The 2006–2007 Kuril Islands great earthquake sequence

Abstract: The southwestern half of a ∼500 km long seismic gap in the central Kuril Island arc subduction zone experienced two great earthquakes with extensive preshock and aftershock sequences in late 2006 to early 2007. The nature of seismic coupling in the gap had been uncertain due to the limited historical record of prior large events and the presence of distinctive upper plate, trench and outer rise structures relative to adjacent regions along the arc that have experienced repeated great interplate earthquakes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 87 publications
8
109
0
Order By: Relevance
“…Very shallow megathrust slip also occurred in the 2006 M w 8.3 Kuril earthquake, an area also lacking in previous interplate seismicity (Ammon et al, 2008;Lay et al, 2009). …”
Section: Coseismic Slip In Aseismic Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very shallow megathrust slip also occurred in the 2006 M w 8.3 Kuril earthquake, an area also lacking in previous interplate seismicity (Ammon et al, 2008;Lay et al, 2009). …”
Section: Coseismic Slip In Aseismic Regionsmentioning
confidence: 99%
“…Normal faulting aftershocks have been observed after many large megathrust ruptures (Fig. 18), particularly those that rupture very shallowly near a trench (e.g., Kanamori, 1971;Christensen and Ruff, 1988;Lin and Stein, 2004;Ammon et al, 2008;Lay et al, 2009;Asano et al, 2011;El Hariri and Bilek, 2011;Bilek et al, 2011;Ide et al, 2011;Kato et al, 2011;Lange et al, 2012;Rietbrock et al, 2012;Yue et al, 2014b;Wetzler et al, 2017;Sladen and Trevisan, 2018). Some of these intraplate extensional events are within the outer rise, seaward of the trench, or on plate-bending related faults below the megathrusts, while others are found within the upper plate adjacent to the zone of high slip (e.g., Farías et al, 2011;Hicks and Rietbrock, 2015).…”
Section: Aftershock Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture duration measurements provided in the literature for ! ≥ 6.5 earthquakes are compared with duration estimated from our time--shift measurements (Abercrombie et al, 2003;Antolik et al, 2006;Houston et al, 1998;Lay et al, 2010a;2010b;Lay et al, 2009;Sladen, 2009a;2009b;2008a;2008b;2007a;2007b;Kikuchi, written communication, 2001;Tanioka and Ruff, 1997;Tocheport et al, 2006;Yagi, 2004;2003;2002). R o m a n c h e 1 9 9 4 S a n t a -C ru z Is .1 9 9 9…”
mentioning
confidence: 99%
“…A large number of studies which focus on the properties of aftershock sequences have been published during the last decades (Tsapanos, 1990(Tsapanos, , 1992Drakatos, 2000;Henry and Das, 2001;Felzer et al, 2004;Shcherbakov et al, 2005;Schorlemmer et al, 2005;Lay et al, 2009;Marsan and Lengliné, 2010;Goda, 2012;Scholz and Campos, 2012;Shcherbakov et al, 2013;MousaviBafrouei et al, 2014;among others). Moment release rates during mainshocks compared with moment release rates during aftershock sequences showed that the moment release rates of aftershock sequence are 30 times smaller than the maximum moment rate of the main shock (Kagan and Houston, 2005) It is well known that aftershock sequences follow statistical laws.…”
Section: Introductionmentioning
confidence: 99%